International Public History (De Gruyter Oldenbourg, 2018)
International Public History is a major stimulus to the field of public history, which has been growing all over the world both as an academic discipline and as a self-identity for its practitioners, and provides a much-needed publishing venue for those engaged in the field. IPH features theoretical, research and "practice-oriented" articles on a wide range of topics. Its e-format offers readers a rich experience through multimodal enhancement.